The Iranian crisis and the birth of the Cold War : the bridge to victory - Harper, Benjamin F. (Lexington Books, 2018)
This study examines the Iranian crisis of 1946 and its role in shaping the dynamics of the Cold War. The author uses the encounter as a case study to analyze how the United States used its atomic monopoly to achieve its international objectives in the early postwar era.